(untitled) (Research, Society and Development, 2022)
Cryptococcus spp affects mainly dogs and cats, however, there are reports in other animal species, such as guinea pigs. The objective of this study is to report a case of a lesion by cryptococcosis in a guinea pig’s auricles. The animal had firm nodules under the touch in both auricles, being one of them with a granulomatous aspect, both ulcerated, with serosanguineous secretion, pain, and associated itching. For the diagnosis, a biopsy was performed for histopathological examination and after a result suggestive of fungal dermatitis by Cryptococcus spp., treatment with itraconazole and adjuvant therapy with Echinacea angustifolia 6CH and Carduus marianus 6CH was initiated, which demonstrated to be effective. Furthermore, we suggest the inclusion of cryptococcosis as a differential diagnosis in cases of auricular lesions in this species.